Laparoscopic cholecystectomy: an experience of university hospital in eastern Nepal - Bajracharya, A; Adhikary, S; Agrawal, CS (Health Renaissance, 2012)
Background: Laparoscopic cholecystectomy has become the standard treatment for symptomatic gall stones disease. Objective: To assess the safety of this procedure, to audit the conversion and bile duct injury rates and the factors which influence these. Methods: Demographics and ethnic group, conversion to open operation and bile duct injury recorded. Pre operative, operative and the relevant data collected prospectively. The X2 test to determine significance of any differences between subgroups. Results: A total of 346 laparoscopic cholecystectomy over a six months period (15 April 2010- 14October 2010), male to female ratio 1:4. The most common indication for surgery was biliary colic/dyspepsia (51%),cholecystitis (chronic- 49.4%, acute-12%), pancreatitis, gallbladder polyp, history of recurrent attacks 16.5%,obesity 19.1%. 128 were operated by consultant, 170 by junior consultants, 48 were by senior residents. There were no statistically significant difference found in the duration of surgery between consultants and junior consultants (P=0.264), however significant between consultants and senior residents (P=<0.001). Over all open conversion rate 2.9%, there was a single case of bile duct injury equating to a bile duct injury rate 0.3%. Conclusion: Despite limited resources, laparoscopic cholecystectomy is feasible and safety procedure for gallstones disease even in developing country like Nepal. DOI: http://dx.doi.org/10.3126/hren.v10i1.6007 HREN 2012; 10(1): 46-48